A dynamically tunable human serum albumin biosensor based on topological edge states graphene nanozyme - Chen, Ling; Yao, Qiaohong; Chen, Jie; Peng, Yuxiang; Xu, Jiao; Fu, Qiang (Frontiers in Bioengineering and Biotechnology, 2026)
This study presents a novel optical biosensor for human serum albumin (HSA) detection utilizing a heterostructure that integrates topological edge states with graphene. The sensor achieves high-sensitivity detection through optical topological modes and enables dynamic system responsiveness via graphene’s tunable conductivity regulated by Fermi level modulation. Numerical results demonstrate that topological edge state excitation induces a sharp reflectance dip (depth >95%) at 195.5 THz in the optical communication band, exhibiting exceptional responsiveness to refractive index variations while maintaining stability against environmental interference through topological protection. Dynamic optimization is realized through electrostatic gating modulation of graphene’s Fermi energy and layer number, with additional sensitivity enhancements achieved via precise control of sensing layer thickness and refractive index. The integration of topological photonics with two-dimensional materials provides a versatile foundation for developing sensing-therapeutic systems that address current challenges in biomedical applications, demonstrating significant potential for integration with nanozyme-based diagnostic and therapeutic nanotechnology. The platform’s exceptional field enhancement and tunability could potentially augment the imaging sensitivity of nanozyme-based contrast agents, while its precise modulation capabilities may improve therapeutic efficiency through optimized catalytic activity. Furthermore, the robust topological protection mechanism offers enhanced stability crucial for clinical translation, addressing key limitations in current nanozyme technology including biocompatibility concerns and inconsistent catalytic performance. This integrated approach opens new possibilities for miniaturized, tunable, and interference-resistant biosensing systems with significant potential for multimodal synergistic applications in clinical diagnostics and environmental monitoring.